Chemotherapy Based on Supramolecular Chemistry: A Promising Strategy in Cancer Therapy - Sherif Ashraf Fahmy; Jana Brüßler; Mohamad Alawak; Mayyada M. H. El-Sayed; Udo Bakowsky; Tamer Shoeib (MDPI AG, 2019)
Chemotherapeutic agents are considered one of the strategies in treating cancer. However, their use is faced by many challenges, such as poor water solubility leading to poor bioavailability and non-selective targeting of cancerous cells leading to diminished therapeutic actions and systemic adverse effects. Many approaches were adopted to overcome these drawbacks and to achieve the targeted delivery of the chemotherapeutic agents to the cancerous cells while minimizing adverse effects. Recently, supramolecular systems such as macrocycles have gained attention in the field of cancer therapy for being able to encapsulate different anticancer drugs via either host-guest complexation or self-assembly leading to a myriad of advantages. This review highlights the most recent studies concerned with the design of such novel systems for cancer therapy.